A water-responsive calix[4]resorcinarene system: self-assembly and fluorescence modulation - Sosa, María Virginia (2024)
This study explores how water content modulates the self-assembly and fluorescence behavior of two novel calix[4]resorcinarene macrocycles. These macrocycles transition from large, flattened structures in pure THF to large giant vesicles (500–5000 nm) coexisting with small micelles (3.4–3.5 nm) as the water percentage in THF/water mixtures increases up to 53%. At higher water percentages, the assemblies become smaller, forming unimodal micelles with diameters of approximately 140–160 nm. Fluorescence quenching is observed upon water addition, attributed to nonradiative deactivation. These findings highlight water as a key regulator of the assembly and fluorescence of these calix[4]resorcinarene macrocycles, paving the way for further development of water-responsive calixarene systems.